Effects of hysteresis on steady-state infiltration in unsaturated slopes - Tami, Denny (2011)
Hysteresis is a common feature exhibited in hydraulic properties of an unsaturated soil. For a specific matric suction, water content or coefficient of permeability on a wetting curve is always lower than those found on a drying curve. This paper focuses on hysteresis observed in steady-state infiltration tests in a laboratory slope model. The slope model consisted of a 400 mm thick fine sand layer overlying a 200 mm thick gravelly sand layer at a slope angle of 30°. The slope model was subjected to artificial rainfalls of different intensities. The slope model was instrumented to continuously measure the changes in pore-water pressure or matric suction, volumetric water content, and water balance during an experiment. Two experiments with similar applied precipitation intensities were conducted on soils that experienced adsorption and desorption processes. For the adsorption process, the slope model was first subjected to an antecedent steady-state rainfall with an intensity lower than the intensity of the incident steady-state rainfall. In the adsorption process, the water content of the soils increased during the incident rainfall prior to achieving the steady-state condition. For the desorption process, the slope model was first subjected to an antecedent steady-state rainfall with an intensity higher than the intensity of the incident steady-state rainfall. In the desorption process, the water content of the soils actually decreased during the incident rainfall prior to achieving the steady-state condition. The results indicate that the matric suction distributions in soils experiencing the desorption process were higher than those observed in soils experiencing the adsorption process. The matric suctions within the slope during a steady-state infiltration were affected by the initial water content of the soil prior to the infiltration process. Numerical analyses, employing both drying and wetting hydraulic properties of the soils, were performed to study the difference in matric suctions as observed in the experiments. The results suggest that the hysteretic behavior of the soil affects the matric suction distribution within the slope at steady-state conditions.